1986
DOI: 10.1029/gl013i011p01133
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic charging and dust transport at Mercury's surface

Abstract: A consideration of the presence of energetic charged particles in the magnetosphere of Mercury and their direct interaction with the planetary surface leads to the tentative conclusion that the nightside hemisphere could be occasionally charged to a surface potential of a few kilo‐Volts. This electrostatic charging process, if feasible, would further imply that electrostatic transport of sub‐micron dust particles on the surface of Mercury could play a significant role in the evolution and modification of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…The electron thermal current is easily much larger, although a detailed estimation is not possible for us as the electrons are not explicitly modelled in the quasi-neutral hybrid code. Thus, on the dayside there is no lack of current carries, but rather there may be a need for potential drops or barriers that limit the electron thermal current and negative charging of the planet (see Ip, 1986, for an analysis of surface charging).…”
Section: Discussionmentioning
confidence: 99%
“…The electron thermal current is easily much larger, although a detailed estimation is not possible for us as the electrons are not explicitly modelled in the quasi-neutral hybrid code. Thus, on the dayside there is no lack of current carries, but rather there may be a need for potential drops or barriers that limit the electron thermal current and negative charging of the planet (see Ip, 1986, for an analysis of surface charging).…”
Section: Discussionmentioning
confidence: 99%
“…[5] Besides Earth's moon, the concept of surface charging has been applied in only a few solar system bodies, such as Mercury [Ip, 1986;Janhunen and Kallio, 2004] and asteroids [Lee, 1996]. Application to asteroids has shown that surface charging may actually be important for electrostatic dust transport [Colwell et al, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…Ip (1986) suggested that the nightside surface of Mercury might be negatively charged (up to perhaps a kilovolt) because of the difference in thermal velocity between ions and electrons. If this were indeed the case, a horizontal electric field would be set up on the dawn and dusk flanks, directed toward the nightside, potentially also contributing to a redistribution of charge, and possibly mapping into the magnetosphere along the magnetic field lines.…”
Section: Surface Charging and Charge Redistributionmentioning
confidence: 98%